KEPEMIMPINAN KEPALA SEKOLAH PEREMPUAN PADA SEKOLAH EFEKTIF - Marhawati, Besse (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2017)
Abstrak: This study aimed to describe the leadership of female principal in effective schoolsof MIT Al-Islah Kota Gorontalo. The approach methodology that used in this study was aqualitative with case study design. Data analysis was performed by the steps: data reduction,data presentation, drawing conclusions or verification of data records that obtained fromobservations and interviews. The results of the study as follows: (1) strategy of the principalwomen in achieving effectiveness in MIT Al-Islah Kota Gorontalo include: (a) optimallearning (b) empowering the potency of the students, and (c) establishing the cooperationwith various partners to support student’s achievement; (2) supporting factors in improvingstudent achievement at MIT Al-Islah Kota Gorontalo that include: (a) inputing data ofstudents who excel and selected that prioritized for RA graduates of Al-Islah, this inputingnot limited insiders but also for for the public by advertising, where ranking system wastaken based on the results of testing that consists of psychological tests (independence) wasused, academic tests (math and reading), testing skills (memorizing short chapters); and (b)obtaining support from the school components.keyword: female school leadership, effective schoolsAbstrak: Penelitian ini bertujuan untuk mendeskripsikan kepemimpinan kepala sekolahperempuan pada sekolah efektif di MIT Al-Ishlah Kota Gorontalo. Pendekatan yangdigunakan dalam penelitian ini adalah pendekatan kualitatif dengan rancangan studi kasus.Analisis data dilakukan dengan langkah-langkah yaitu: reduksi data, penyajian data,penarikan kesimpulan atau verifikasi yang diperoleh melalui catatan hasil observasi danhasil wawancara. Hasil penelitian sebagai berikut: (1) strategi kepala sekolah perempuandalam mencapai sekolah efektif di MIT Al-Ishlah Kota Gorontalo yang meliputi: (a)optimalisasi pembelajaran, (b) memberdayakan potensi siswa, dan (c) menjalin kerja samadengan berbagai pihak untuk mendukung prestasi siswa; (2) faktor- faktor pendukung dalammeningkatkan prestasi siswa di MIT Al-Ishlah Kota Gorontalo meliputi: (a) input siswayang unggul dan terseleksi, diprioritaskan bagi lulusan RA Al-Ishlah, tetapi juga terbukauntuk umum melalui iklan dengan sistem rangking yang didasarkan pada hasil testing yangterdiri tes psikologi (kemandirian), tes akademik (berhitung dan membaca), tes keterampilan(hafalan surah pendek); dan (b) memperoleh dukungan dari komponen sekolah.Kata kunci: kepemimpinan kepala sekolah perempuan, sekolah efektif